TUBERCULAR TESTICULAR ABSCESS: A CASE REPORT - Parse, Rocci Jack; Agil, Ahmad (Indonesian Journal of Urology, 2022)
Objective: This study aims to provide fellow physicians a better insight in diagnosing and managing similar cases. Case(s) Presentation: A 36 year old male presented to the emergency department with a chief complaint of red, painful, and progressively enlarging swelling of the left scrotal pouch since 1 week ago. The patient had a history of similar complaint and recurrent cloudy urine which were left untreated 1 year before. Based on physical examination and ultrasonography findings, the patient was diagnosed with left scrotal abscess and was treated by incisional drainage of abscess and necrotomy debridement under spinal anesthesia. Discussion: Tuberculosis infection of scrotal contents is rare and occurs in approximately 7% of the patients with tuberculosis, although tuberculosis itself is a global epidemic with more than 2 billion of the world population infected. In patients with genital tuberculosis, pulmonary and renal tuberculosis can be documented in 50% and 80-85% respectively. It is often secondary to the pre-existing tuberculosis of the urinary tract, which may be confirmed by the culture of early morning urine specimens. Conclusion: Treatment of testicular abscess is administration of appropriate antibiotics according to its causative organism accompanied by surgical drainage. Early diagnosis and prompt treatment of testicular abscess is necessary, since chronic and severe cases, as happened in this patient, usually resulted in nonviable testicular tissue and necessitate orchidectomy. This may be due to cumulative ischemia of the testicles from multiple mechanisms: inflammatory infiltration causing compression of the spermatic cord, thrombosis secondary to venous congestion and/or bacterial exotoxins.